The Influence of Gene Polymorphism OPRM1 118A/G on the Perception of Pain and Pharmacodynamics of Narcotic Analgesics - V. M. Zhenilo; O. A. Makharin (Общая реаниматология)
The polymorphism of μ-opioid receptor is one of the most studied polymorphisms that affect the activity of narcotic analgesics. Despite that there are a large number of publications dealing with the problem, the obtained results are not being currently used in clinical practice. The purpose of this review is to describe the impact of this polymorphism on the perception of pain and sensitivity to narcotic analgesics. It is shown that patients with the G118G genotype of μ-opioid receptor are tolerant to narcotic analgesics and need a larger dose to achieve the desired effect than that in normal genotype. At the same time, the likelihood of side effects associated with the use of narcotic analgesics does not significantly differ between the carriers of normal genotype and those of the A118G, G118G genotypes.